Colonic mucosa–associated lymphoid tissue lymphoma: A case report - Chen, Dan; Zhong, Ding-Fu; Yang, Yi; Chen, Si-Shuang; Liu, Dong (Frontiers in Surgery, 2023)
Background Mucosa-associated lymphoid tissue (MALT) lymphoma is a group of extranodal lymphomas that originate from B cells. Primary colonic MALT lymphoma is a rare disease, and there is no consensus on its endoscopic features and standard therapies. It is essential to raise awareness of colonic MALT lymphoma and choose the appropriate treatment. Case presentation In this case report, we describe a 0-IIb-type lesion that was found by electronic staining endoscopy and magnifying endoscopy. The patient underwent a definitive diagnostic ESD for diagnosis. The patient was evaluated for lymphoma after diagnostic ESD according to the Lugano 2014 evaluation criteria, which are divided into imaging remission on the basis of CT and/or magnetic resonance imaging (MRI) evaluation and metabolic remission on the basis of PET-CT evaluation. Based on the PET-CT results suggesting increased glucose metabolism in the sigmoid colon, the patient underwent additional surgical treatment. According to the pathological results of the surgery, we found that ESD could treat such lesions, which may provide a new option for colorectal MALT lymphoma. Conclusion The low incidence of colorectal MALT lymphoma, especially for 0-IIb lesions, which are difficult to detect, requires the use of electronic staining endoscopy to improve the detection rate. The combination with magnification endoscopy can improve the understanding of colorectal MALT lymphoma, which ultimately requires pathological support for diagnosis. According to our experience with the present patient case, ESD seems to be a feasible and economical choice for the treatment of massive colorectal MALT lymphoma. However, the combined application of ESD and another therapy scheme needs further clinical investigation.